Supercritical carbon dioxide extraction of cannabinoids from Cannabis sativa L. - Rovetto, Laura Jorgelina (2017)
Cannabis sativa L. extracts with high concentration of δ9-tetrahydrocannabinolic acid (THCA) and δ9-tetrahydrocannabinol (THC) were obtained by supercritical carbon dioxide (CO2) extraction. The objective of this work was to investigate the cannabinoid concentration of the extracts, the overall process yield under different extraction conditions, and the effect of ethanol as co-solvent. Extraction experiments were carried out with multistage pressure increments and at constant pressure of 17, 24 and 34MPa and 328K with flow rate of 200g/min of CO2. At 34MPa apparent solubilities of extracts were determined for four different Cannabis sativa L. strains with variable cannabinoids initial content. Extraction yield was highly dependent on pressure and plant material starting composition. The use of ethanol as a co-solvent was investigated with two different approaches, i.e. constant co-solvent flow, and by applying pulses of ethanol at different times though the extraction procedure. The obtained extracts were fractionated in 3 separators in a cascade configuration of decreasing temperature and pressure. The cannabinoid composition of the extracts was determined with HPLC analysis. Process extraction efficiency as high as 92% was achieved.